Library online database system (LODS) for undergraduate students to support studies and research: the users evaluation - Zulkifli, Zahidah; Azlan, Nor Athira (Faculty of Information and Communication Technology International Islamic University Malaysia, 2019)
Library online database system (LODS) has been developed to support the process of studies and research among undergraduate (UG) students. This paper reports on the user evaluation results that examine participants’ acceptance. The objectives of the user evaluation are to ensure that the new system does what it sets out to do and meets the requirements of the business. A single case study has been employed in this evaluation which included UG students from International Islamic University Malaysia (IIUM) as participants. The user evaluation was carried out in two phases, which involved a task-based approach and a questionnaire. The user acceptance test of the LODS in serving the UG students has been reflected by the positive feedback from the 15 participants. From the findings, in general, the system has been perceived as useful to support studies and research works among undergraduate students electronically.